External evaluations in LOMCE: transparency in rural education? - Santamaría Luna, Rogeli (Avances en Supervisión Educativa, 2015)
This document is intended to reflect on some articles of the Organic Law 2/2006 of 3 May on Education last modified by Organic Law 8/2013, of 9 December, to improve educational quality. We have selected those linked to external evaluation and transparency were discussed. In turn, the publication of Law 19/2013, of December 9, transparency, access to public information and good governance, imposes new obligations on the administrations and should result in the availability and dissemination of reports, as well as results. Both laws can promote knowledge of rural school if current approaches to external evaluation in Spain who do not usually attend rural uniqueness or do so partially. Thus they contribute to hiding the rural school or show a negative image of it because they have poorly contextualized results.